Effect of shock waves on macrophages: A possible role in tissue regeneration and remodeling. (December 2015) - Sukubo, Naths Grazia; Tibalt, Elisabetta; Respizzi, Stefano; Locati, Massimo; d'Agostino, M.Cristina
Abstract: Introduction: Extracorporeal Shock Wave Therapy (ESWT) is broadly used as a non-surgical therapy in various diseases for its pro-angiogenic and anti-inflammatory effects. However, the molecular mechanisms translating tissue exposure to shock waves (SW) in a biological response with potential therapeutic activity are largely unknown. As macrophages take part in both the onset and amplification of the inflammatory response, and well in its resolution, we investigated the effect of SW on their biology. Methods: Human monocyte-derived macrophages were polarized to classic (M1) pro-inflammatory macrophages or alternative (M2) anti-inflammatory macrophages and exposed to SW ad different intensities. Expression levels of marker genes of macrophage activation were measured by qPCR at different time points. Results: SW did not induce activation of resting macrophages at any energy level used. Conversely, when used at low energy SW caused a significant inhibition of some M1 marker genes (CD80, COX2, CCL5) in M1 macrophages and a significant synergistic effect for some M2 marker genes (ALOX15, MRC1, CCL18) in M2 macrophages. SW also affected cytokine and chemokine production, inducing in particular a significant increase in IL-10 and reduction in IL-1β production. Conclusions: Macrophage exposure to low energy SW dampens the induction of the pro-inflammatory profile characterizing M1 macrophages and promotes the acquisition of an anti-inflammatory profile synergizing with macrophage alternative activation. Highlights: We report the effects of Shock Waves (SW) on macrophages activity in vitro. SW did not induce activation of resting macrophages. Low energy SW dampens the induction of the pro-inflammatory profile in M1 macrophages. Low energy SW promotes the acquisition of an anti-inflammatory profile with M2 macrophages.